BEHAVIOR OF THE DIAMETRIC DISTRIBUTION OF ECOLOGICAL GROUPS IN A MIXED OMBROPHILOUS FOREST FRAGMENT - Oliveira, Thiago Wendling Gonçalves de; Schmitz, Rafael; Camaño, Jorge Danilo Zea; Corte, Ana Paula Dalla; Sanquetta, Carlos Roberto (Floresta, 2018)
The Mixed Ombrophilous Forest is one of the most threatened ecosystems in Brazil. It is thus necessary to understand its dynamics of growth over time so that sustainable use and conservation management strategies be proposed. The objective of this study is to evaluate the behavior of the diametric distribution of two pioneer and non-pioneer ecological groups in a fragment of Mixed Ombrophilous Forest considering four years of evaluations: from 2002 to 2017. Exponential, Gamma, Weber and Weibull 3P density probability functions were adjusted. The diametric behavior of the forest and the ecological groups analyzed remained negative exponentially, being a characteristic of natural forests. The distributions that best adjusted were Weibull 3P for the forest as a whole and for the group of pioneers, and Weber for non-pioneers. We concluded that ecological groups have the same pattern of diametric distribution as the forest as a whole. However, different forest management strategies are necessary considering the intrinsic characteristics of each group.